Towards evidence-based guidelines for the prevention of venous thromboembolism: systematic reviews of mechanical methods, oral anticoagulation, dextran and regional anaesthesia as thromboprophylaxis. - Roderick, P; Ferris, G; Wilson, K; Halls, H; Jackson, D; Collins, R; Baigent, C (2005)
OBJECTIVES: To assess the benefits in terms of reductions in the risks of deep vein thrombosis (DVT) and of pulmonary embolism (PE), and hazards in terms of major bleeding, of: (i) mechanical compression; (ii) oral anticoagulants; (iii) dextran; and (iv) regional anaesthesia (as an alternative to general anaesthesia) in surgical and medical patients. DATA SOURCES: Electronic databases, search of Antithrombotic Trialists' Collaboration database, contact with trialists and manufacturers. REVIEW METHODS: All trials identified as fitting the selection criteria were independently assessed. The primary outcomes were DVT, PE and major bleeding events, and proximal venous thrombosis (PVT) and fatal PE were secondary outcomes. Trials were subdivided into those that had assessed a method as the only means of thromboprophylaxis ('monotherapy') and those that had assessed the effects of adding a method to another form of thromboprophylaxis ('adjunctive therapy'). RESULTS: Mechanical compression methods reduced the risk of DVT by about two-thirds when used as monotherapy and by about half when added to a pharmacological method. These benefits were similar irrespective of the particular method used (graduated compression stockings, intermittent pneumatic compression or footpumps) and were similar in each of the surgical groups studied. Mechanical methods reduced the risk of PVT by about half and the risk of PE by two-fifths. Oral anticoagulants, when used as monotherapy, reduced the risk of DVT and of PVT by about half, and this protective effect appeared similar in each of the surgical groups studied. There was an apparently large four-fifths reduction in the role of PE, but not only was the magnitude of this reduction statistically uncertain, but also pulmonary embolism was reported by a minority of trials, so it may be subject to selection bias. Oral anticoagulant regimens approximately doubled the risk of major bleeding and appeared less effective at preventing DVT than heparin regimens, although were associated with less major bleeding. Dextran reduced the risk of DVT and of PVT by about half, again irrespective of the type of surgery, but too few studies had reported PE to provide reliable estimates of effect on this outcome. Dextran appeared to be less effective at preventing DVT than the heparin regimens studied. Dextran was associated with an increased risk of bleeding, but too few bleeds had occurred for the size of this excess risk to be estimated reliably. Compared with general anaesthesia, regional anaesthesia reduced the risk of DVT by about half, and this benefit appeared similar in each of the surgical settings studied. Regional anaesthesia was associated with less major bleeding than general anaesthesia. CONCLUSIONS: In the absence of a clear contraindication (such as severe peripheral arterial disease), patients undergoing a surgical procedure would be expected to derive net benefit from a mechanical compression method of thromboprophylaxis (such as graduated compression stockings), irrespective of their absolute risk of venous thromboembolism. Patients who are considered to be at particularly high risk of venous thromboembolism may also benefit from a pharmacological thromboprophylactic agent, but since oral anticoagulant and dextran regimens appear less effective at preventing DVT than standard low-dose unfractionated heparin or low molecular weight heparin regimens, they may be less suitable for patients at high risk of venous thromboembolism, even though they are associated with less bleeding. Whenever feasible, the use of regional anaesthesia as an alternative to general anaesthesia may also provide additional protection against venous thromboembolism. There is little information on the prevention of venous thromboembolism among high-risk medical patients (such as those with stroke), so further randomised trials in this area would be helpful.